Poor cognitive flexibility in eating disorders: examining the evidence using the Wisconsin Card Sorting Task. - Kate Tchanturia (Public Library of Science (PLoS), 2012)
Background People with eating disorders (ED) frequently present with inflexible behaviours, including eating related issues which contribute to the maintenance of the illness. Small scale studies point to difficulties with cognitive set-shifting as a basis. Using larger scale studies will lend robustness to these data. Methodology/principal findings 542 participants were included in the dataset as follows: Anorexia Nervosa (AN) n = 171; Bulimia Nervosa (BN) n = 82; Recovered AN n = 90; Healthy controls (HC): n = 199. All completed the Wisconsin Card Sorting Task (WCST), an assessment that integrates multiple measurement of several executive processes concerned with problem solving and cognitive flexibility. The AN and BN groups performed poorly in most domains of the WCST. Recovered AN participants showed a better performance than currently ill participants; however, the number of preservative errors was higher than for HC participants. Conclusions/significance There is a growing interest in the diagnostic and treatment implications of cognitive flexibility in eating disorders. This large dataset supports previous smaller scale studies and a systematic review which indicate poor cognitive flexibility in people with ED.